The Influence of the Tikrar Method on the Ability to Memorize the Al-Qur'an Mahasantri at Ma'had 'Aly Al-Husnayain Surakarta - Mushlihah Listyaningrum; Mukhlis Fathurrahman; Lailla Hidayatul Amin (Edumaspul: Jurnal Pendidikan, 2023)
There are many different methods that can be used in the process of memorizing the Qur'an, including the pledge method. The purpose of this research is to determine the application of the pledge method to female students, to determine the ability to memorize the Al-Qur'an for female students, and to determine the effect of the vow method on the ability to memorize the Al-Qur'an for female students. This research uses quantitative methods. Consists of two variables. The Tikrar method is the independent variable and the ability to memorize the Qur'an is the dependent variable. Data collection techniques used are questionnaires and documentation. while the data analysis technique used is the descriptive quantitative data analysis technique. The results of this study indicate that the tikrar method used by female students at Ma'had 'Aly Al-Husnayain in memorizing the Qur'an is included in the high category with a percentage of 45%. Students' ability to memorize the Qur'an at Ma'had 'Aly Al-Husnayain is included in the very high category with a percentage of 43%. While the results of the calculation of the hypothesis test with product moment correlation obtained a significance value of 0.431. While the Rtable value at 1% significance is 0.304 and at a 5% significance level is 0.312, then the result is that the significance value is greater than the significance value of 1% or 5% or Rtable < R count so that the hypothesis reads "The tikrar method affects the ability to memorize the Qur'an mahasantri Ma'had 'Aly Al-Husnayain Surakarta for the academic year 2022 /2023” is not proven true or the hypothesis is rejected. And the influence of the pledge method on the ability to memorize the Qur'an has been carried out using a simple linear regression equation, Y = a + bX, = 70.2 + 0.355.